Low cardiac vagal tone index by heart rate variability differentiates bipolar from major depression. (28th May 2019) - Hage, Brandon; Britton, Briana; Daniels, David; Heilman, Keri; Porges, Stephen W.; Halaris, Angelos
Abstract: Objectives: Major depressive disorder (MDD) and depression in bipolar disorder (BD) are often difficult to distinguish from each other. Autonomic nervous system (ANS) dysregulation is associated with various depressive symptoms and inflammatory response disinhibition. The beat-to-beat pattern of heart rate (heart rate variability, HRV) offers a non-invasive portal to ANS function and provides a reliable index of resting cardiac vagal tone. We quantified HRV and measured inflammatory biomarkers in MDD and BD patients in an effort to derive potential diagnostic criteria for MDD and BD. Methods: Sixty-four MDD and 37 BD patients were enrolled. HRV was assessed and blood was drawn at baseline after antidepressant washout and prior to study initiation. HRV was quantified and corrected for artefacts. Results: MDD subjects had significantly higher baseline respiratory sinus arrhythmia ( P = 0.05) and LF-HRV ( P < 0.01) in comparison to BD subjects. Compared to MDD subjects, BD subjects had significantly higher baseline levels of IL-10 ( P < 0.01) and MCP-1 ( P < 0.01). In the MDD group only, baseline LF-HRV was significantly positively correlated to baseline levels of IL-10 ( r = 0.47, P < 0.01). Conclusions: Reduced vagal tone and higher levels of inflammatory biomarkers may distinguish BD from MDD and reveal an underlying pathophysiology of depression involving ANS dysfunction and chronic immune system dysregulation.